If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14x-146=6x-10
We move all terms to the left:
14x-146-(6x-10)=0
We get rid of parentheses
14x-6x+10-146=0
We add all the numbers together, and all the variables
8x-136=0
We move all terms containing x to the left, all other terms to the right
8x=136
x=136/8
x=17
| 9•20=(x-2)(x+6) | | 59+(3x+1)=180 | | O.25+1.5=n+0.25 | | 5-9d=-10d | | 4z+4=6z-5 | | 9x20=(x-2)(x+6) | | -3g-9=3 | | 7q-35=4q+4 | | 〖45x〗^2-6x-24=0 | | 6y^2−7y+2=0 | | -16x+4x=-32+18x | | 6y2−7y+2=0 | | |x-3|=-9 | | 6(3x^2)=4x^-2 | | 9z=25 | | 3y=12-12 | | 3x+3=3(x-9) | | ((10t+8)/6)-4=2t+2 | | (12x+8)+(8x-8)=90 | | 1.2x+2x+4=-4.8 | | 6-(4n-2)=5-5n | | 5x+3+42=90 | | 3(x-7)+9=3x-12 | | F=8f+9 | | 7n+9=33 | | 3x+6/2×=3 | | 4v-17=59 | | -(7x+7)=-6x+8 | | 2.5x-6.6=15.9 | | 20=5^2x | | 7x+7(4x+1)=-273 | | x^2-6x-16/x^2-10=1 |